Mengkiritisi Banyaknya Peraturan Daerah Bermasalah - Thalhah, Muhammad (Unisia, 2012)
Parallel with the regional autonomy in the post-reformation era, regional governments and parliaments enthusiastically produce regulation as tools of fund-raising to support their regional development projects and welfares. Unfortunately, these promulgated regulations have, to large extent, breached both formal and substantial principles as legal products have to be. As a consequence, these legal products are, indeed, contra productive with the ends of achieving people welfares. Keywords: Regional autonomy, regulations, welfares.